THE SIMULATION OF P-PERSISTENT CSMA ALGORITHM OF UNEQUAL RANDOM MULTIPLE ACCESS - Dadenkov, S. A. (Radio Electronics, Computer Science, Control, 2018)
Context. The relevance of the simulation of p-persistent CSMA algorithm of unequal random multiple access is caused by importance of accounting personal node priorities for execution of adequate assessment of probable and time response characteristics of information transfer in designing widespread fieldbus-networks LonWorks, BacNet, etc. The aim of this work is to obtain analytical expressions for estimating probabilities of successful and failed node access to the channel, the transmission time information in the network with equal and unequal rivalry of nodes based on p-persistent and predictive p-persistent CSMA algorithms of random multiple access. Method. The method of probability theory has been used there to solve problems. The analysis of equal and unequal multiple access ppersistent CSMA nodes in the saturation mode of the channel by the transmission with a constant number of node-rivals has been executed. A method of estimating the time of successful transmission of information by the node through an average number of cycles of rivalry and probabilistic characteristics of the access nodes has been proposed. Expressions to estimate the necessary probabilistic and time characteristics were obtained: the average length of transmission and time of information transmission by the node, the effective bandwidth. The proposed method mainly differs from analogs by the possibility of characteristics estimation of information transmission given the manifold priorities of the network nodes, which improves the accuracy of the performed calculations. Results. The analytical expressions have been received, quantification and analysis of probabilistic and temporal characteristics of information transfer in a network with equal and unequal random multiple p-persistent CSMA access has been performed. Conclusions. The simulation results of equal and unequal rivalry network channel illustrate the importance of taking into account individual priorities of the nodes in the network. The feasibility of using access priorities is the need to transfer important information on the background of universal low-priority data. The significance of the results is to perform an adequate quantitative assessment of the characteristics of information transmission in a channel with equal and unequal parties.